2020
DOI: 10.2196/15726
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to an Online Demonstration of the Effect of Increased Fruit and Vegetable Consumption on Appearance: Survey Study

Abstract: Background Inadequate fruit and vegetable consumption causes a considerable disease burden and premature mortality. Despite public health promotion of a healthy diet, the average consumption is still below recommended levels. Fruit and vegetable consumption influences human skin color, increasing red/yellow/orange pigment in the skin. Given that this color is deemed attractive and healthy-looking, the appearance benefit may motivate to eat more fruit and vegetables. Such appearance motivation could… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Notably, focusing research efforts on clarifying the aspects of lifestyle that are critical for facial attractiveness could also have important public health implications. For example, using computer graphic methods to model the positive effects of increased fruit and vegetable consumption on facial appearance has been shown to be an effective intervention for improving diet, particularly in young adults [12]. Thus, focusing research effort on better understanding the links between lifestyle and facial attractiveness could not only increase our understanding of the factors that shape a critical driver of social perceptions and stereotypes, but might also illuminate novel approaches to improving public health.…”
mentioning
confidence: 99%
“…Notably, focusing research efforts on clarifying the aspects of lifestyle that are critical for facial attractiveness could also have important public health implications. For example, using computer graphic methods to model the positive effects of increased fruit and vegetable consumption on facial appearance has been shown to be an effective intervention for improving diet, particularly in young adults [12]. Thus, focusing research effort on better understanding the links between lifestyle and facial attractiveness could not only increase our understanding of the factors that shape a critical driver of social perceptions and stereotypes, but might also illuminate novel approaches to improving public health.…”
mentioning
confidence: 99%
“…There have been numerous studies that have suggested that individuals’ perceptions of physical fitness are influenced by skin color ( Carrito et al, 2016 ; Dias, 2020 ), and physical fitness has important implications for resisting potential threat and harm ( Ogunjimi et al, 2020 ). One study showed that when participants were asked to select the healthiest person from photographs of individuals with different skin color, they consistently chose dark skin over fair or wheatish skin ( Cairns et al, 2020 ). Furthermore, individuals with slightly dark skin (which may indicate more efficient blood circulation) were considered more attractive and healthy ( Jones, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This concern is not only for fresh tropical fruits but also for their juices. The impact of this demand in the developed countries has promoted production and processing capacity, assuring the offering of these products in the international market (Cairns et al, 2020, Silva e Claro, 2019, Sugerman et al, 2011, Maia et al, 2009.…”
Section: Introductionmentioning
confidence: 99%